Students' Critical Thinking Ability with Google Classroom-Assisted Project Based Learning and Inquiry Learning Models - Yossi Novita; Kashardi Kashardi; Jayanti Syahfitri (Jurnal Pendidikan Biologi, 2022)
Covid-19 pandemic has a major impact on the world of education. Learning system that was previously carried out face to face was required to be carried online learning considering the social distancing rules. Project based learning and inquiry learning were used because they were appropriate for learning from home using google classroom and contributing to improve student’s critical thingking ability. This study aims to determine 1) differences in students' critical thinking abilities with the application of the Project based learning model (PjBL), Inquiry and Conventional using Google Classroom media in Biology learning at SMA Negeri 4 Rejang Lebong, 2) a more effective learning model to improve reasoning and critical thinking skills. This research is a quasi experimental research. The population in this study were students of class X IPA SMA Negeri 4 Rejang Lebong. The research sample was determined by simple random sampling, in order to obtain class X IPA 1 and X IPA 2 as the experimental class and class X IPA 3 as the control class. The data collection method used an essay test with 5 items. Then the data were analyzed using one way ANOVA followed by the LSD test. The results showed that there were differences in students' critical thinking abilities in the application of the Project Based Learning (PjBL) model, inquiry learning and conventional learning assisted by Google Classroom. The PjBL and Inquiry models are better at improving students' critical thinking abilities compared to conventional learning. This research provides benefits for students to improve critical thinking ability.